Stress relaxation test for sago–wheat mixtures gel - Sarker, Md. Zaidul Islam; A., Abdul Karim; D. M., A. Manan; Nik Ab Rahman, Nik Norulaini; Abdul Kadir, Mohd. Omar (Taylor and Francis, 2003)
Viscoelastic properties of sago starch and wheat flour, and sago–wheat flour mixtures at different percentages of sago substitution were studied. Swelling characteristics of high protein wheat (HPW), medium protein wheat (MPW) and low protein wheat (LPW) flour, and sago starch were determined at various temperatures (55 –95 C). Both sago and wheat starch granules started to swell from 55 C and reached a maximum at 75 C. Flour gels containing mixture of sago þ wheat of different protein content at different levels of sago substitutions were prepared as follows: sago þ HPW, sago þ MPW, and sago þ LPW flours. Stress relaxation (SR) test for control sago and control wheat flours and sago–wheat mixtures were carried out at different percentages of sago substitutions from 10 to 50%. For control flours the value of asymptotic residue modulus, E A for HPW and MPW was rapidly increased with the increase of the gel concentration up to 30% but it decreased at 20%. For LPW it decreased at 20 and 25%, and increased at 30%. At higher percentage of sago in the mixture, E A value does not show uniform consistence pattern. It was found to increase rapidly at 50% of sago portion for all types of wheat flour.